A label-free fluorescent aptasensor based on a novel exponential rolling circle amplification for highly sensitive ochratoxin A detection. (1st June 2023) - Zhu, Daozhong; Huang, Ting; Zhou, Qianying; Yang, Zizhong; Liu, Birong; Li, Minmin; Li, Chunrong; Chen, Jin-Xiang; Dai, Zong; Chen, Jun
Highlights: The ERCA aptasensor was simple, rapid and label-free. The ERCA with exponential signal amplification enabled OTA detection down to 4.3 fg/mL. The attachment of OTA and aptamer achieved highly specific detection of OTA. The ERCA strategy possessed great accuracy comparable to HPLC. Abstract: Rapid and sensitive analysis of ochratoxin A (OTA) plays an important role in food safety. Here, an aptasensor based on novel exponential rolling circle amplification (ERCA) was proposed for ultrasensitive and label-free fluorescence detection of OTA. The attachment of OTA to its aptamer could release H and rapidly hybridize with CT to initiate rolling circle amplification (RCA). The amplicons could further displace H from APH to initiate recycled RCA, achieving exponential growth of amplification products that contained G4 dimers for lighting up ThT. Benefiting from the exponential amplification efficiency of the ERCA strategy and the high fluorescence quantum yield of G4 dimer/ThT, this strategy exhibited a wide linear range from 10 fg/mL to 10 ng/mL with a detection limit of 4.3 fg/mL. In addition, the aptasensor displayed satisfactory recoveries in real sample analysis. We believe that this novel aptasensor possesses promising application prospects in food safety and medicine detection.